Identification of the Critical Nontechnical Skills for Surgeons Needed for High Performance in a Variable-resource Context (NOTSS-VRC). Issue 6 (December 2019) - Scott, John W.; Lin, Yihan; Ntakiyiruta, Georges; Mutabazi, Zeta; Davis, William A.; Morris, Megan A.; Smink, Douglas S.; Riviello, Robert; Yule, Steven
Abstract : Objective: To identify the critical nontechnical skills (NTS) required for high performance in variable-resource contexts (VRC). Background: As surgical training and capacity increase in low- and middle-income countries (LMICs), new strategies for improving surgical education and care in these settings are required. NTS are critical for high performance in surgery around the world. However, the essential NTS used by surgeons operating in LMICs to overcome the challenges specific to their contexts have never been described. Method: Using a constructivist grounded theory approach, 52 intraoperative team observations as well as 34 critical incident interviews with surgical providers (surgeons, anesthetists, and nurses) were performed at the 4 tertiary referral hospitals in Rwanda. Interview transcripts and field notes from observations were analyzed using line-by-line coding to identify emerging themes until thematic saturation was achieved. Results: Four skill categories of situation awareness, decision-making, communication/teamwork, and leadership emerged. This provided the framework for a contextually informed skills taxonomy consisting of 12 skill elements with examples of specific behaviors indicative of high performance. While the main skill categories were consistent with those encountered in high-income countries, the specific behaviors associated with these skills often focused on overcoming the frequently encountered variability in resources, staff, systems support, and language in this context. Conclusion: This is the first description of the critical nontechnical skills, and associated example behaviors, used by surgeons in a VRC to overcome common challenges to safe and effective surgical patient care. Improvements in the NTS used by surgeons operating in VRCs have the potential to improve surgical care delivery worldwide.